Income inequality analysis : Panel data approach - Kharebava, Salome; Formánek, Tomáš; Holý, Vladimír; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2023)
This paper analyzes income inequality and the potential economic and social factors that contribute to it through the use of panel data analysis. It compares various methods of measuring income inequality and investigates how income inequality is related to economic development, education, the labor market, globalization, and demographic changes. The research specifically concentrates on high-income countries and employs the Gini coefficient and Palma ratio as independent variables in two regression models. The paper highlights potential limitations and sources of error in the analysis and proposes future research directions, including the use of mixed effects modeling and dynamic long panel models. The conclusions drawn from this study may have important implications for policymakers looking to address income inequality.
Vedoucí práce: Tomáš Formánek
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2023
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2023
Způsob přístupu: Internet
Keywords: data analysis and modeling [obor dipl. práce]; diplomové práce; master's theses